Prevalence, associated factors and clinical features of congenital syphilis among newborns in Mbarara hospital, Uganda - Sam Oloya; David Lyczkowski; Patrick Orikiriza; Max Irama; Yap Boum; Richard Migisha; Julius P. Kiwanuka; Juliet Mwanga-Amumpaire (BMC, 2020)
Abstract Background While congenital syphilis is a significant public health problem that can cause severe disabilities, little is known about the situation in Uganda. We describe prevalence, associated factors and clinical presentation of congenital syphilis in Mbarara, Uganda. Methods A cross sectional study was carried out among mother- newborn dyads from the postnatal ward of Mbarara Regional Referral Hospital (MRRH). After obtaining informed consent, a structured questionnaire was used to capture data on risk factors for congenital syphilis. A finger prick was performed on the mothers for Treponema Pallidum Haemagglutination Assay (TPHA). If TPHA was positive, a venous blood sample was collected from the mother to confirm active infection using Rapid Plasma Reagin (RPR). Venous blood was drawn from a newborn if the mother tested positive by TPHA and RPR. A newborn with RPR titres 4 times higher than the mother was considered to have congenital syphilis. We fit logistic regression models to determine factors associated with congenital syphilis. Results Between June and September 2015, we enrolled 2500 mothers and 2502 newborns. Prevalence of syphilis was 3.8% (95% CI 3.1-4.6) among newborn infants and 4.1% (95% CI 3.4-5.0) among their mothers. Maternal age <25 years, past history of genital ulcer, a past history of abnormal vaginal discharge, and not receiving treatment of at least one of genital ulcer, genital itching, lower abdominal pain and abnormal vaginal discharge in the current pregnancy were the risk factors associated with congenital syphilis. The most common clinical feature was hepatosplenomegaly. Conclusions We found higher-than-expected syphilis sero-prevalence rates in a high risk population of postnatal mothers and their newborns in Uganda. Bridge populations for syphilis may include mothers not tested during pregnancy, who are usually married and not treated. In accordance with our results, the national policy for syphilis control in Uganda should be strengthened to include universal syphilis screening amongst mother-newborn pairs in postnatal clinics with subsequent partner notification.